The Digital Social Capital and GIG Economy Participation on The Level of Online Consumption of Students in Surabaya - Febriandita Tedjomurti; Permata Ayu Widyasari (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
The digital revolution has ushered in profound changes across social and economic landscapes worldwide, with especially significant impacts in the rapidly urbanizing contexts of the Global South. In these regions, digital platforms have become central to reshaping not only economic activities but also the fabric of social relationships and consumption patterns. In cities such as Surabaya, Indonesia, these changes are particularly salient among university students, a demographic that navigates the intersections of education, labor precarity, and digital connectivity. The study examines the interplay between digital social capital and gig economy participation to understand their combined influence on online consumption behaviors among students in Surabaya. Quantitative methods were used in this study, with 70 respondents, measured using a 5-point Likert scale through a questionnaire instrument that had been tested for validity and reliability. The results of this study indicate that both digital social capital and gig economy participation are important factors that influence online consumption behavior of students in Surabaya, both partially and simultaneously. It shows how digital transformation is not only changing consumption patterns, but also how social capital is built and utilized and how new forms of work are emerging in developing countries.